DEVELOPMENT OF LEARNING MEDIA BASED ON VIRTUAL LABORATORY IN PHYSICS PRACTICUM - Adelita Putri Noviana (Program Studi Pendidikan Fisika, FITK, UNSIQ, 2022)
This research is motivated by the lack of use of learning media, especially physics subjects at SMA Makassar Raya. This study aims to analyze the effectiveness of virtual laboratory-based learning media in physics practicum. The type of research used is Research and Development (R&D) research. The research was conducted at SMA Makassar Raya for two weeks in November 2021 with a sample of 20 students. The research method used is a 4D model which includes Define, Design, Development, and Disseminate. The results showed that the virtual laboratory-based learning media was declared valid with a value of V> 0.4 based on the Aiken's V expert agreement index analysis test. Learning media was declared practical, based on the results of the responses of teachers and students who were in the very good category or the responses given were positive. . Learning using virtual laboratory-based learning media is said to be effective and can improve psychomotor abilities. The effectiveness of virtual laboratory-based learning media in learning is shown from practicum activities and physics learning test results with a percentage of 65%.